Comparing coal and 'transition materials'? Overlooking complexity, flattening reality and ignoring capitalism. (July 2022) - Dunlap, Alexander; Marin, Diego
Abstract: This article highlights the misleading calculations, reductions and overstatements of the recent Perspective article: 'More transitions, less risk: How renewable energy reduces risks form mining, trade and political dependence' by Jim Kane and Robert Idel. While in theory we might agree with the general claim of Jim Kane and Robert Idel 'that a transition from coal to wind involves an enormous decrease in mined materials', we demonstrate that this claim is misleading. This article stresses five essential points to correct their analysis and calculations in order to offer approximations that are more accurate and, thus, revealing the extent of complications and problems facing real energy transition. This entails challenging the fossil fuel versus renewable energy dichotomy; critically interrogating data and research scope; acknowledging the realities of capitalism; paying closer attention to policy objectives; and recognizing the underexplored reality of green extractivism. This is done not only to encourage environmental and energy policy taking ecological crises seriously, but also—more immediately—to prevent the misuse and decontextualization of Jim Kane and Robert Idel's claims to advance the agendas of socially and ecologically destructive companies.